2013
DOI: 10.1108/ijwbr-2012-0007
|View full text |Cite
|
Sign up to set email alerts
|

The wine consumption preferences of young people: a Spanish case study

Abstract: PurposeThis paper aims to analyze the current wine consumption situation with special attention being paid to the habits and preferences of young consumers.Design/methodology/approachThe study was carried out on a sample of 318 consumers; 50 per cent of the sample were under the age of 35 and 50 per cent were older. The information gathered was then subjected to the appropriate statistical tests. The lifestyles and images of wine consumption of those surveyed was first looked at, followed by the results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
3
15
0
4
Order By: Relevance
“…Finally, their results did not find any significant effect from appellations. A similar conclusion is obtained by Garcia et al (2013), which found a diffused lack of knowledge among younger Spanish wine consumers about quality designations, suggesting promotional activities could be strengthened within this scope. A result also confirmed in the French market, where the youngest consumers look at price as the most salient factor for purchasing decisions, with ROO just in second place, while the oldest consumers recognized ROO as the most relevant factor (Ginon et al, 2014).…”
Section: The Quality Predictor Of Geographical Cues According To Consumers' Agesupporting
confidence: 81%
“…Finally, their results did not find any significant effect from appellations. A similar conclusion is obtained by Garcia et al (2013), which found a diffused lack of knowledge among younger Spanish wine consumers about quality designations, suggesting promotional activities could be strengthened within this scope. A result also confirmed in the French market, where the youngest consumers look at price as the most salient factor for purchasing decisions, with ROO just in second place, while the oldest consumers recognized ROO as the most relevant factor (Ginon et al, 2014).…”
Section: The Quality Predictor Of Geographical Cues According To Consumers' Agesupporting
confidence: 81%
“…The most general conclusion about this generational segment is that they have a growing interest in wine, they are willing to spend much money on wine, and their wine consumption differs from that of previous generations (Hall et al, 2004;Thach and Olsen, 2006). Previous studies on these consumers have focused on their interaction with wine, wine preference, consumption, and purchasing behaviour (Agnoli et al, 2011a;Ritchie, 2011;Marinelli et al, 2013); differences in wine behaviour from older generations (Qenani-Petrela et al, 2007;Fountain and Lamb, 2011;Chrysochou et al, 2012;Garcia et al, 2013); lifestyle and attitudes regarding wine (Bruwer and Li, 2007;Charters et al, 2011); importance given to wine attributes (Chrysochou et al, 2012;Hristov and Kuhar, 2014a); and knowledge, purchase risk, and information search (Li et al, 2011;Atkin and Thach, 2012;Hammond et al, 2013). Although a number of studies have been conducted for this generational cohort in the field of wine worldwide, limited knowledge exists in the countries emerging from the dissolution of Yugoslavia.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete choice models are an adequate methodology for the analysis of consumers' decisions in which they must choose an option from among a finite set of alternatives. These models have been used in many areas and also in the analysis of wine consumers' preferences (De Magistris et al, 2011, 2015Escobar et al, 2018;García et al, 2013;Guris et al, 2007;Gustavsen and Rickertsen, 2018;Martínez-Carrasco et al, 2006;Rodríguez-Donate et al, 2017;Selvanathan and Selvanathan, 2004).…”
Section: Modelmentioning
confidence: 99%